KANIKOSEN (KOBAYASHI TAKIJI) “BACAAN LIAR” TAHUN 1920-AN DALAM RENTANG SEJARAH JEPANG - Muhammad Reza Rustam (Universitas Diponegoro, 2016)
This paper describes a dynamics proletarian literature and its relationship with Kanikosen novel by Kobayashi Takiji, including; the institution, ideology, production, and figures associated to narration used by Marxism theory posed by the author as one of the Japan